The genomic landscape of Nepalese Tibeto-Burmans reveals new insights into the recent peopling of Southern Himalayas - Gnecchi-Ruscone, Guido A. (Sci Rep, 2017)
While much research attention has focused on demographic processes that enabled human diffusion on the Tibetan plateau, little is known about more recent colonization of Southern Himalayas. In particular, the history of migrations, admixture and/or isolation of populations speaking Tibeto-Burman languages, which is supposed to be quite complex and to have reshaped patterns of genetic variation on both sides of the Himalayan arc, remains only partially elucidated. We thus described the genomic landscape of previously unsurveyed Tibeto-Burman (i.e. Sherpa and Tamang) and Indo-Aryan communities from remote Nepalese valleys. Exploration of their genomic relationships with South/East Asian populations provided evidence for Tibetan admixture with low-altitude East Asians and for Sherpa isolation. We also showed that the other Southern Himalayan Tibeto-Burmans derived East Asian ancestry not from the Tibetan/Sherpa lineage, but from low-altitude ancestors who migrated from China plausibly across Northern India/Myanmar, having experienced extensive admixture that reshuffled the ancestral Tibeto-Burman gene pool. These findings improved the understanding of the impact of gene flow/drift on the evolution of high-altitude Himalayan peoples and shed light on migration events that drove colonization of the southern Himalayan slopes, as well as on the role played by different Tibeto-Burman groups in such a complex demographic scenario.